2004
DOI: 10.1352/0895-8017(2004)109<186:nsarff>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Risk Factors for Chronic Disease in Urban-Dwelling Adults With Down Syndrome

Abstract: Nutritional status and biochemical risk factors for chronic disease were assessed in 48 community-dwelling adults with Down syndrome in the Chicago area. Dietary intake was measured using a food frequency questionnaire completed by the participant's primary caregiver; anthropometric measures included height and weight and waist circumference. Plasma glucose and lipid concentrations were assessed following a 10-hour fast. Overall, 89% of participants were overweight or obese, 54% had large waist circumferences,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
52
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 33 publications
10
52
1
3
Order By: Relevance
“…The mean WC reported in a USA sample of men and women with Down syndrome was 100.4cm and 104.1cm, respectively; 5 whereas in this study mean WC measures were 83.7cm for men and 80.5cm for women. The proportion of adults with WC measures indicative of abdominal obesity in the USA study among persons with Down syndrome 5 was 54% compared to 21% in the present study (19.6% for men and 24.5% for women). This large disparity in the rate of abdominal obesity was also evident among women with intellectual disabilities in general from Taiwan, where the reported rate was 59%.…”
Section: Resultscontrasting
confidence: 76%
See 3 more Smart Citations
“…The mean WC reported in a USA sample of men and women with Down syndrome was 100.4cm and 104.1cm, respectively; 5 whereas in this study mean WC measures were 83.7cm for men and 80.5cm for women. The proportion of adults with WC measures indicative of abdominal obesity in the USA study among persons with Down syndrome 5 was 54% compared to 21% in the present study (19.6% for men and 24.5% for women). This large disparity in the rate of abdominal obesity was also evident among women with intellectual disabilities in general from Taiwan, where the reported rate was 59%.…”
Section: Resultscontrasting
confidence: 76%
“…This is of particular concern since evidence suggests that among those who are overweight, high WC is a strong predictor of adverse metabolic profiles. 31 Although there is some preliminary evidence that higher WC is associated with adverse metabolic and cardiovascular outcomes among adults with intellectual disabilities, 5,8 considerably more work needs to be done to document the health risks associated with abdominal obesity in this population, particularly with clinical sub-groups that may not show the same metabolic profile as others with intellectual disability. For example, Braunschweig and colleagues 5 found that the risk factors for Type 2 diabetes and cardiovascular disease were within a desirable range among adults with Down syndrome, despite high rates of overweight, obesity, and abdominal obesity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Population-level prevalence data indicate that the obesity levels of adults with ID are either similar to or higher than their non-ID counterparts [Emerson, 2005;Yamaki, 2005]. Lack of healthy eating habits and regular physical activity, common factors associated with obesity in the general population [U.S. Department of Health and Human Service, 2001], are also growing problems among persons with ID [Draheim et al, 2002;Braunschweig et al, 2004;Emerson, 2005].Obesity results in significant societal and personal costs [Poston and Foreyt, 1999]. Among persons with ID, it has the potential to reduce or limit opportunities for various types of community participation, including employment and leisure.…”
mentioning
confidence: 99%